EFEK PEMBERIAN REBUSAN KULIT MARKISA UNGU (PASSIFLORA EDULIS) SEBAGAI ANTIDIABETIK TERHADAP GAMBARAN HISTOPATOLOGI PANKREAS TIKUS YANG DIINDUKSI STREPTOZOTOSIN - USWATUL KHOIROT; EMNI PURWONINGSIH; HUMAIRAH MEDINA LIZA LUBIS; LITA SEPTINA (JURNAL ILMIAH KOHESI, 2021)
DM is one of the greatest health problems around the world. Nowdays, we found many studies proved many plants whichcontain antioxidant have a potential as antidiabetic. Antioxidants are able to repair oxidative stress in pancreatic beta cellsthat overcome pancreatic tissues damage. One of the plant that contains rich antioxidant is purple passion fruit ( Passifloraeduils). This study used True Experimental method, with Post –Test Only Control Group Design, which only gave anobservation to a control group after being given a treatment. The sample of this study was white Wister strain male rats(Rattus Norvegisus L). The statistic study of this research used Kruskal Wallis and Mann-Whitney with a significance level ofp > 0,05, because the data were not normally distributed. Pancreatic histopathology improvement in the first treatment groupshowed a non-significant difference compared with positive controlled group (p< 0, 05). Pancreatic histopathologyimprovement in the second treatment group showed a significant different compared with positive controlled group(p< 0, 05). There was an effect of giving purple passion fruit skin decoction (Passiflora eduils) as anti-diabetic to the ratpancreas histopathology that inducted by streptozotosin.